2021
DOI: 10.3389/fped.2021.718647
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Experiments for Hypospadias Surgery: Systematic Review and Quality Assessment

Abstract: Background: There is a steadily growing number of different reconstructive surgical procedures for hypospadias that were tested on animal models prior to their human application. However, the clinical translatability and reproducibility of the results encountered in preclinical urethral reconstruction experiments is considered poor, with significant factors contributing to the poor design and reporting of animal experiments. Our objective was to evaluate the quality of the design and reporting in published art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Preclinical studies play an important role in scientific progress and the discovery of new and potentially successful treatments, assuming that they are designed, conducted, evaluated, and adequately reported in accordance with internationally agreed guidelines. 35 Fundamental experimental design components are often overlooked in scientific papers, which result in such studies being uninterpretable and difficult to reproduce, 6 and preclinical studies on acupuncture for cancer pain do not appear to be an exemption.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies play an important role in scientific progress and the discovery of new and potentially successful treatments, assuming that they are designed, conducted, evaluated, and adequately reported in accordance with internationally agreed guidelines. 35 Fundamental experimental design components are often overlooked in scientific papers, which result in such studies being uninterpretable and difficult to reproduce, 6 and preclinical studies on acupuncture for cancer pain do not appear to be an exemption.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments on animals are rare, poorly reported, less detailed and not reproducible (as a review found) (259). A single urethral reconstruction is reported in a rabbit model.…”
Section: Animal Modelsmentioning
confidence: 99%